2015
DOI: 10.1016/j.psyneuen.2015.04.004
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere length and telomerase in a well-characterized sample of individuals with major depressive disorder compared to controls

Abstract: Background Leukocyte telomere length (LTL) is a marker of cellular turnover and oxidative stress. Studies suggest major depressive disorder (MDD) is associated with oxidative stress, but examinations of MDD and LTL have yielded mixed results, likely because of differences in measurement methods and unmeasured confounding. This study examined LTL and telomerase activity in 166 individuals with MDD compared to 166 age- and gender-matched matched controls free of any psychiatric disorder, using well-validated ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 58 publications
(79 reference statements)
1
38
1
Order By: Relevance
“…Methods have been described elsewhere (Simon et al, 2015). Participants were assessed for psychiatric disorders in person by trained, experienced doctoral-level (MD or PhD) clinicians, using the Structured Clinical Interview for DSM-IV (SCID; First et al, 2002), who also completed interviewer-rated measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods have been described elsewhere (Simon et al, 2015). Participants were assessed for psychiatric disorders in person by trained, experienced doctoral-level (MD or PhD) clinicians, using the Structured Clinical Interview for DSM-IV (SCID; First et al, 2002), who also completed interviewer-rated measures.…”
Section: Methodsmentioning
confidence: 99%
“…Use of any psychiatric medication in the 2 weeks (4 weeks for fluoxetine) prior to screen or of anti-inflammatory medications in the 3 days prior to blood draw was exclusionary (prior use of psychiatric medications was allowed). In case of an acute infection, systematically assessed by a trained clinician using the Cumulative Illness Rating Scale (CIRS), or of antibiotic use, participants returned for phlebotomy 1 week after symptom resolution or completion of any antibiotics (Simon et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have investigated TL in relation to numerous psychiatric disorders [2, unpublished], and several studies have shown shortened TL in MDD [613], although exceptions exist [1416]. Shortened LTL in MDD and other psychiatric disorders could have pathophysiological significance by indicating accelerated aging at the cellular level and by synergizing with depression diagnosis in predicting mortality in certain populations [17].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, [33] concurrently assessed telomere length and telomerase activity in individuals presenting clinically significant, chronic major depressive disorder and matched controls but failed to provide strong evidence of an association of major depressive disorder with shorter LTL, while telomerase activity was lower in men with major depressive disorder. Despite that result, [34], from a comprehensive meta-analysis, described the significant relationship between depression and shorter telomere length as consistent with the notion positing that psychological distress, such as experienced in depression, results in physiological changes leading to shortened telomere length.…”
mentioning
confidence: 99%